An Economics Analysis of Dumping and Antidumping - Li, Yan (2012)
This thesis involves building an own economics model of dumping and antidumping. It analyzes the statistics of WTO antidumping measures and finds the distribution pattern of dumping cases. It analyzes the dumping motive of a rational firm by applying the economics concepts of fixed cost and variable cost and gives an explanation for the distribution pattern of dumping cases from the perspective of economics. It considers the possible interactions of two or more exporting firms by applying game theory, followed by the analysis of the influence of antidumping regime on firms’ strategies.